Onconephrology 2022: An Update. Issue 2 (9th February 2023) - Bonilla, Marco; Gudsoorkar, Prakash; Wanchoo, Rimda; Herrmann, Sandra M.; Jhaveri, Kenar D.
Abstract : Onconephrology is an upcoming and expanding subspecialty that deals with the intersections between hematology/oncology and nephrology. With the paradigm shift in the understanding of cancer immunobiology and mechanisms of oncotherapeutic drug toxicities, it is important for a nephrologist to have a sound understanding of this field. Over the last 5 years, there have been immense developments in our understanding of kidney-related adverse events from various targeted, immuno- and cellular-based therapies. Pathogenic mechanisms of electrolyte imbalance, hypertension (oncohypertension), and AKI from multiple forms of cancer therapies have been explored. Significant research has also been conducted in the field of transplant onconephrology. In this review, we have tried to assimilate the most recent updates in the last 2 years in this ever-growing and fascinating field.